Colostrum: The Golden Elixir of Health – Unveiling Its Multifaceted Benefits in Modern Medicine - Michalska, Martyna; Winiarek, Karolina; Wardyn, Wiktor; Tokarczyk, Elżbieta; Ziemińska, Daria; Guzowski, Cezary; Burczyk, Rafał; Murawska, Joanna (Quality in Sport, 2024)
Introduction: Colostrum is uniquely rich in immunoglobulins, growth factors, antibacterial peptides, probiotics, prebiotics, and essential vitamins and minerals. Available as a supplement, BC is used to prevent gastrointestinal infections, boost immune support, and aid in managing chronic inflammation, autoimmune diseases, and even athletic recovery. Aim: The aim of this article is to assess the potential benefits of colostrum across various health areas, including gastrointestinal health, immune system support, respiratory diseases, dermatology, autoimmune conditions and the development of preterm infants. The article will also present a critical analysis of current scientific data and examine future research directions and therapeutic advancements. Review methods: This article is based on a comprehensive, non-systematic review of the scientific literature. A thorough search of the PubMed database was conducted, and 45 sources published up to 2024 were analyzed to ensure that the information presented is current and relevant. Abbreviated description of the state of knowledge: Analysis of the literature suggests that colostrum may provide passive protection, reduce inflammation and support gut integrity in preterm infants. Inflammatory bowel disease may benefit from colostrum, though results for IBS are mixed. It aids wound healing, has anti-aging effects, and shows potential in autoimmune disease management. It also boosts respiratory immunity and aids athletes' recovery and performance. Conclusions: Colostrum contains bioactive components like immunoglobulins, lactoferrin, and growth factors. While current studies highlight its benefits in enhancing immunity, supporting gut health, and managing inflammatory conditions, more comprehensive clinical trials are required to confirm its efficacy and safety across various populations and health conditions.